EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (BERPIKIR, BERPASANGAN, DAN BERBAGI PENGETAHUAN) DAN CERAMAH TERHADAP HASIL BELAJAR EKONOMI - Efi Nuraini (Jurnal Pendidikan Insan Mandiri, 2012)
This research aims to find out: (1) there is any differences effect or not between use cooperative learning model type think pair share and speech about the economic learning output, (2) effectiveness of cooperative learning model type think pair share in economic learning.This research using experiment method with pretest posttest control-group design. Methods of data gathering techniques used are the test and documentation methods. Data analysis technique used is two tails t test and right side t test with the standards of significance 0.05.Based on the results of data analysis and discussion in this research, it can be concluded that: (1) There are different effect between use of cooperative learning model think pair share type and speech, (2) Cooperative learning model think pair share tipe more effective than speech. Mean of cooperative learning model think pair share type higher than speech. The different mean show that the used of cooperative learning model think pair share type better than speech.The implication: (1) Economic learning output would better by using appropriate learning model,such as cooperative learning models type think pair share, (2) input for economic teacher to use variation learning models in learning activity. An suggestion: (1) For headmaster, add to tool and infrastructure in order to prop up effectiveness learning, (2) For teacher, cooperative learning models type think pair share can be one of choice learning models in learning activity, (3) For student, to optimize and more active in learning activity.Keywords: Cooperative Learning Model, Think Pair Share, Learning Output.